Children and the Dark Side of Human Experience Confronting Global Realities and Rethinking Child Development - Garbarino, James (Springer New York : Imprint: Springer, 2008)
Their haunting images appear on millions of television screens and in newspapers worldwide: Children huddled in refugee camps and exposed to violence in war zones. Children burdened by the emotional and physical scars of violent homes and communities. Children exploited by crass commercialism around the world and around the corner. Too many children are confronting life-threatening risks and experiencing trauma. Synthesizing insights from psychology and philosophy with his own wide-ranging, first-hand experiences around the world, Dr. James Garbarino takes readers on a personalized journey into the dark side of human experience as it is lived by children. In these highly readable pages, Dr. Garbarino intertwines a discussion of children's material and spiritual needs with a detailed examination of the clinical knowledge and experiential wisdom required to understand and meet complex developmental needs. Fusing anecdotal observations, empirical evidence, and an ecological perspective, he reveals a path to ensuring the fundamental human rights of all children: the right to safety, to equality, to economic parity, and to a meaningful life. Dr. Garbarino's challenge to his readers: If we are to succeed in making a lasting, positive change in the lives of children, we must be willing to rethink the concepts of development, trauma, and resilience. Children and the Dark Side of Human Experience is must-reading for all mental health professionals, educators, researchers, social workers, child advocates, and policymakers - in fact, for anyone who takes an interest in the well-being and future of the world's children.